Esporte educacional: uma proposta gímnica para o Programa Segundo Tempo no Estado do Ceará - Reis, Lorena Nabanete dos (2011)
Facing the reality of social inequality in Brazil, several public and private initiatives are taken, trying to overcome the current state. The Second Time Program, proposed by the Ministry of Sport, aims to democratize the sport quality education for children and adolescents at social risk. Considering the significant educational values of general gymnastics, this research aims to examine the feasibility of a gymnastic proposal for the Second Time Program through the gymnastics in the state of Ceará. The research is characterized as quasi-experimental (Gressler, 2004), is the type of study, for example, evaluating the effect of a method of teaching in classes for a previously structured system. Initially, from a literature search, based on educational proposals in the country drew up a gymnastics proposal for the Program, which was later developed into core of the Secretariat of Sports of the State of Ceará, with children aged 10 and 13 years of age. This process lasted for 20 meetings, in which were developed by the monitor of the core, general gymnastics activities aiming at the experience of bodily elements, acrobatic exercises and exploration equipment. After the development of classes, were done semi-structured interviews with students and with the monitor in order to check the meaning of general gymnastics classes for children as well as to view the display on the feasibility of the proposal. The data collected in the interviews was done through content analysis of Bardin (1977). The results showed that the main meanings of practice for students, issues such as socialization, enjoyment of activity and body development. The monitor, from the results of the interview, consider the viable development of the relation between this proposal and the objectives of the Second Half Program, indicates positive aspects for children as socialization and opportunity to meet new event. After analysis of the experience as a whole, the study highlights the need for educational care, dealing with the training of professionals who will work directly with children and adolescents, the structural conditions as well as the objectives and methodological strategies of the core which must be consistent with the proposal. Thus, we concluded this work, considering viable the development of this gymnastic proposal program of work for the Second Time Program through gymnastics, since there are constant monitoring bodies, as well as attention to the issues cited.